Biogas energy potential in Riau Indonesia - Mel, Maizirwan; Ihsan, Sany Izan; Adesta, Erry Yulian Triblas (2010)
The increasing of crude oil prices recently in the world, the need for an alternative source of fuel in the Indonesia is urgently required. In addition, growing concern about climate change is driving the need for “low-carbon” fuels. One highly potential form of renewable and low-carbon fuel is biogas from anaerobic digestion of organic wastes. Anaerobic digestion is a naturally occurring process of decomposition of organic matter by microbes in an oxygen-free environment. Anaerobic digestion has been used throughout the globe for many years, especially in areas outside of the Indonesia. However, it has not been applied widely for production of biogas as a power generator fuel. Millions of tons of wastes are generated each year from agricultural, municipal, and industrial sources. Agricultural wastes such as palm oil mill effluent (POME) and Sago mill effluent can be used as the feedstock to produce biogas. The waste can be converted into usable biogas through anaerobic digestion. This can reduce the adverse impact on the environment and can be used on the farm to take care of a part, if not all, of its energy needs. In addition, biogas can be cleaned and upgraded to biomethane, a gas indistinguishable from conventional natural gas that can be used as a fuel. The purpose of this paper is to introduce a potential biogas production from agricultural wastes and conversion to a fuel. In order to understand the potential of biogas production, we provide a brief overview of the two main stages such as production of biogas via anaerobic digester and the uses of biogas as fuel for power generator.